Territorialiser la domination ethnique : le ghetto musulman de Juhapura à Ahmedabad (Inde) - Charlotte Thomas (L'Espace Politique)
This article analyses the spatial dynamics underneath the pogroms that took place in 2002, in Gujerat, India. Attacks were carried by Hinduist militants and solely targeted Muslims. Based upon a long-term ethnography, the article assesses the specific case of Ahmedabad, the economic main city of Gujerat. It defends the main argument that the specific location of violence nurtured a unique dynamic of segregation. Namely, the systematic targeting of mixed areas –spaces that were lived by both Hindus and Muslims– pushed the Muslim minority to gather in a peripheric area named Juhapura. Hence, high-, middle- and low-casts Muslims all gathered at the same place to look for a safe and secure ethnic entre-soi. This is an unprecedent reconfiguration of Indian residential patterns for space was traditionally organized according to economic cleavages, not ethnic ones. I analyze this newly constituted territory as a ghetto (Wacquant) and consider it to be a spatial dispositive of domination in a Foucaldian sense. From a Hinduist perspective, the ghetto intends to dominate the Muslim minority. One of the main features of the ghetto is indeed the selective neglect from the authority that its inhabitants have to face. But the lack of public amenities pushes them to manage the territory of the ghetto by themselves. In an apparent paradox though, by doing so the inhabitants consequently reverse the identity stigma that goes with the fact of living in a ghetto. Ultimately, they hence resist the domination that the ghetto aims at exerting on them via the ghetto.